2014
DOI: 10.3389/fnhum.2014.00865
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the dichotomy between vegetative state and minimally conscious state: a review of the statistical evidence

Abstract: Given the enormous consequences that the diagnosis of vegetative state (VS) vs. minimally conscious state (MCS) may have for the treatment of patients with disorders of consciousness, it is particularly important to empirically legitimate the distinction between these two discrete levels of consciousness. Therefore, the aim of this contribution is to review all the articles reporting statistical evidence concerning the performance of patients in VS vs. patients in MCS, on behavioral or neurophysiological measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 104 publications
5
25
0
1
Order By: Relevance
“…Reviewing neurophysiological as well as behavioural evidence regarding the distinction between VS and MCS, these authors found that no combination of variables allowed for a reliable and consistent differentiation of the two diagnostic categories. Although unexpected, our results integrate very well with these findings, and support the need of a more diversified and multi-faceted evaluation procedure in DOC patients (Liberati et al, 2014).…”
Section: Real 15supporting
confidence: 86%
See 1 more Smart Citation
“…Reviewing neurophysiological as well as behavioural evidence regarding the distinction between VS and MCS, these authors found that no combination of variables allowed for a reliable and consistent differentiation of the two diagnostic categories. Although unexpected, our results integrate very well with these findings, and support the need of a more diversified and multi-faceted evaluation procedure in DOC patients (Liberati et al, 2014).…”
Section: Real 15supporting
confidence: 86%
“…While the above discussion focused on properties of our paradigm, a recent review by Liberati et al (2014) questioned the validity of assuming a dichotomy between VS and MCS altogether. Reviewing neurophysiological as well as behavioural evidence regarding the distinction between VS and MCS, these authors found that no combination of variables allowed for a reliable and consistent differentiation of the two diagnostic categories.…”
Section: Real 15mentioning
confidence: 98%
“…By definition, although some may follow commands to a certain degree, accurate communication is not possible. VS and MCS most likely exist on a spectrum rather than being categorically distinct 15 16. Thus, patients may be classified into MCS plus (ie, if they are able to obey commands) or minus (ie, if they only localise pain, exhibit visual pursuit or show appropriate emotional expressions) 17.…”
Section: Methodsmentioning
confidence: 99%
“…The authors identified a number of structures whose resting state activity was significantly decreased in patients as compared with healthy controls. On the other hand, they did not find convincing differences between UWS and MCS, which was in line with Liberati et al (5). Kondziella et al (7) came, however, to a different conclusion that brain connectivity data in rest and under passive stimulation (but not in active instruction conditions) reliably differ between UWS and MCS.…”
Section: (P 22)]mentioning
confidence: 50%